2001
DOI: 10.1007/s007260170065
|View full text |Cite
|
Sign up to set email alerts
|

The relation between glutamine and the immunodepression observed in exercise

Abstract: Glutamine is the most abundant amino acid in the body. It is an important fuel for some key cells of the immune system. Both the plasma concentration of glutamine and the functional ability of immune cells in the blood are decreased after prolonged, exhaustive exercise. Glutamine feeding has had beneficial effects in clinical situations, and the provision of glutamine after intensive exercise has decreased the incidence of infections, particularly of upper respiratory tract infections. However, the precise eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
0
19
0
2
Order By: Relevance
“…Variation in glutamine concentration over time was not significant in the BCAA trial, and it was significantly higher in the BCAA than in the placebo trial from 0 to 2 h after exercise, indicating that the BCAA supplement suppressed the exercise-induced decreases in plasma glutamine concentrations. Plasma glutamine is known as an important substrate for immune cells (9,10). Therefore, BCAA supplementation before exercise may play a role in supporting the immune system, although the relation between plasma glutamine levels and exercise-induced immune suppression is still controversial (11,12).…”
Section: Resultsmentioning
confidence: 99%
“…Variation in glutamine concentration over time was not significant in the BCAA trial, and it was significantly higher in the BCAA than in the placebo trial from 0 to 2 h after exercise, indicating that the BCAA supplement suppressed the exercise-induced decreases in plasma glutamine concentrations. Plasma glutamine is known as an important substrate for immune cells (9,10). Therefore, BCAA supplementation before exercise may play a role in supporting the immune system, although the relation between plasma glutamine levels and exercise-induced immune suppression is still controversial (11,12).…”
Section: Resultsmentioning
confidence: 99%
“…74 Muscle tissue is the main glutamine depot containing 90% of the body's glutamine reserves and during catabolic stress in humans, muscles are a primary organ of glutamine synthesis and release to the blood. 75,76 Glutamine is the most abundant free amino acid in the body and it is critical for the proper functioning of the immune cells that utilize it at high rates for antigen presentation and cytokines production. 77,78 In addition, macrophage-derived cytokine stimulates glutamine synthesis in muscle cells.…”
Section: A Correspondence Between Immune and Muscle Cellsmentioning
confidence: 99%
“…It was found that the reduction of the glutamine concentration in an in vitro culture resulted in a decline in the pace of mononuclear blood cells division and reduced phagocytosis and cytokine production by macrophages [74]. On the basis of these reports, it can be assumed that the changes in the levels of glutamine could contribute to the weakening of the immune system observed after exercise [73].…”
Section: Metabolic Changesmentioning
confidence: 99%
“…This amino acid is the energy source for the immune system cells. Reducing the level of glutamine after a marathon may persist for 6-9 hours after the end of a run [73]. In addition, glutamine is a nitrogen source for purine and pyrimidine nucleotides synthesis, which facilitates proper proliferation of lymphocytes.…”
Section: Metabolic Changesmentioning
confidence: 99%